Concurrent highly pathogenic avian influenza H5N1 virus and Salmonella pullorum infections: unusual mortality patterns in Rhode Island red birds in India: a case study - Shreeniwas Singh; Soumajit Sarkar; Sandip Garai; Sunita Kumari Murmu; Saroj Kumar Thakur; Shreya Sinha; Amit Kumar Jha; K. C. Nikhil (Discover Viruses)
Abstract The bacteria of the genus Salmonella and the avian influenza virus (AIV) are two major microbial pathogens of poultry. They impose significant risks to public health. In this case study, low mortality was observed in brooders, growers, and 10-week-old Rhode Island Red poultry in two different farms in Jharkhand, India. Both farms were well-spaced and housed mixed poultry flocks under standard hygienic practices. Farm A had a total of 1197 birds, including Rhode Island Red, Kadaknath, and White Leghorn breeds. Farm B housed a total of 5000 birds, comprising commercial broilers, Sonali chicken breed, and Khaki Campbell ducks. Farms A and B used a deep litter system with separate compartments for each breed/species under one roof. The post-mortem, initial bacteriological investigations, and invA gene-targeted PCR indicated an infection with Salmonella spp. Later, subtype-specific RT-PCR has confirmed the co-infection with Highly Pathogenic Avian Influenza Virus (HPAI H5N1). Surprisingly, the overall mortality was 5.60% and observed only in the Rhode Island Red birds. Upon confirmation of HPAI H5N1, immediate infection control and outbreak prevention measures were implemented, including culling, disinfection, movement restrictions, and surveillance. Despite multiple risk factors like large flock size, mixed breeds, and vulnerable birds, the mortality rate was surprisingly low. The co-infection appeared to reduce virus spread, severity, and mortality in Rhode Island Red poultry.